(untitled) (Research, Society and Development, 2021)
In recent decades, implantology has been widely used in the rehabilitation of endentulous areas. One of the essential conditions for implant placement is sufficient bone height. When this condition is not met, the procedure for lifting or elevating the maxillary sinus is proposed. This elevation can be achieved by using the side window approach or “direct sinus elevation”, which is a traumatic surgical technique that allows an increase in the amount of bone in the posterior jaw.Therefore, this research seeks to know the technique of the side window, aiming to clarify its benefits, indications and limitations. In addition, it presents a bibliographic review based on the literature and articles published on platforms such as Pub Med, Scielo and Google Scholar in the last 10 years. It was possible to verify that, among the several existing surgical techniques for the lifting of the maxillary sinus, the lateral window approach has been shown to be the best, given its bone grafting capacity to reach high heights. High success rates depend on an adequate diagnosis, clinical, surgical management and trained professionals.